Non conventional psychiatric rehabilitation in schizophrenia using therapeutic riding: the FISE multicentre Pindar project - Stefania Cerino; Francesca Cirulli; Flavia Chiarotti; Stefano Seripa (Istituto Superiore di Sanità, 2011)
The FISE (Federazione Italiana Sport Equestri) Pindar is a multicentre research project aimed at testing the potential effects of therapeutic riding on schizophrenic patients. Twenty-four subjects with a diagnosis of schizophrenia were enrolled for a 1 year-treatment involving therapeutic riding sessions. All subjects were tested at the beginning and at the end of treatment with a series of validated test batteries (BPRS and 8 items-PANSS). The results discussed in this paper point out an improvement in negative symptoms, a constant disease remission in both early onset and chronic disease subjects, as well as a reduced rate of hospitalization.